FY 2021-FY 2023 Medium-Term Budget. - International Monetary Fund. Office of Budget and Planning (Washington, D.C. : International Monetary Fund, 2020)
On April 27, 2020, the Executive Board of the International Monetary Fund (IMF) approved the IMF's administrative and capital budgets for financial year (FY) 2021, beginning May 1, 2020, and took note of indicative budgets for FY 2022-23.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet